Education about, in, and for wetlands: practices, premises, possibilities, and challenges - Marcinkowski, Tom (Frontiers in Water, 2025)
The purpose of this paper is to review areas of educational theory, research, and practice relevant to wetlands education, notably education about, in, and for wetlands. Five key areas are reviewed: (a) from the Report of the Intergovernmental Conference on Environmental Education, goals and objectives for wetlands education; (b) from the literature, major curricular and instructional approaches in and elements of wetlands education; (c) from the literature, broad instructional strategies available to and commonly used in wetlands education; (d) from websites of federal agencies in the U.S., education, outreach, and training programs that focus on education about, in, and for inland and coastal wetlands; and (e) from print and electronic sources, a sample of curricular and instructional materials that pertain to education about, in, and for inland and coastal wetlands. Each area is summarized in the form of a list or table. The paper concludes with a series of challenges which hold implications for education policy makers, program developers and providers, instructional staff, assessment and evaluation specialists, scientists, and others who collaborate on and work to advance wetlands education at the local, national, regional, and global levels.